Network Management Project in BioCen - Rodríguez González, Ihosvany (2021)
BioCen is a scientific institution made up of several production units that are dedicated to different lines in the Cuban biotechnology and pharmaceutical universe. To guarantee the security and management of the information generated in the institution, and to reduce the impact of IT risk, it has a set of tools, procedures and strategies, collected in a network management project that is updated every year. The project includes everything related to the configuration, structure, control and monitoring, both of the data network, the process network, and the Wi-Fi network; in addition to the organization of services, servers, and the systems that comprise them. This paper presents the management tools used in BioCen for the control and monitoring of the services provided on the network, its internal and external traffic; as well as the detection of incidents. Examples of monitoring and control are shown with the management tools that are applied in some functional areas, as well as the design of the local BioCen network. Finally, the tests carried out on the network system, internal audits, statistical analysis of services and response to incidents are addressed.